A High‐Performance Direct Methanol Fuel Cell Technology Enabled by Mediating High‐Concentration Methanol through a Graphene Aerogel. Issue 10 (26th July 2018) - Liu, Xiaoteng; Xi, Jiabin; Xu, Ben Bin; Fang, Bo; Wang, Yucheng; Bayati, Maryam; Scott, Keith; Gao, Chao
Abstract: A facile methodology to fabricate graphene aerogel (GA), and its application in a direct methanol fuel cell (DMFC), is demonstrated for the first time. A new GADMFC design is proposed by using GA to replace two main components within the DMFC—the gas‐diffusion layer and the flow field plate. The results indicate a 24.95 mW cm −2 maximum power density of air polarization is obtained at 25 °C. The membrane electrolyte assembly has a 63.8% mass reduction compared to an ordinary one, which induced 3 times higher mass power density. Benefiting from its excellent organic solvent absorbency, the methanol crossover effect is dramatically suppressed while using 12m methanol, therefore, a higher concentration or even pure methanol can be refilled into the fuel cell. Due to the excellent fuel‐storage function of the GA, the methanol cartridge and complicated fuel circulation system in the DMFC can be eliminated, which can reduce the manufacturing cost for DMFCs. It is expected this research will promote the application of GA in fuel‐cell applications, as well as shed light on the novel fuel‐cell technology to address future energy challenges. Abstract : A graphene aerogel is used to replace the gas‐diffusion layer and flow field plate of a direct methanol fuel cell (DMFC). Compared to traditional DMFCs, the mass power density is three‐times improved with dramatically suppressed methanol crossover effect while using 12m methanol as the fuel. It also shows fuel‐storage function, and therefore the methanol cartridge and fuel‐circulation system can be eliminated.